Analiza wpływu algorytmów sterowaniana wybrane właściwości impulsowych sterowników prądu przemiennego - Kasperek, Radosław
Goals of the thesis were analisys and comparative simulation tests of influence of modified control algorithms on energetic properties of the pulse AC line conditioners(ACLC). Scope of the thesis: analisys of current state and description of ACLC properties; development of energetic properties of PACLC by dead time elimination, inactive components of load voltage (current) elimination, implementation of random PWM techniques; analysis of EMI, laboratory tests of the model.
Keywords: algorytm sterowania; sterownik prądu przemiennego; napięcie przemienne